Ferroptosis in pain: evidence, challenges, and opportunities - Yan, Qianqian; Wang, Fang; Liu, Mengyuan; Mao, Jinyan; Zhao, Zihao; Wang, Bo (Frontiers in Immunology, 2025)
Pain, an unpleasant but essential feeling for life, affects more than 20% of the global population and burdens health and the economy. Due to the lack of understanding of the exact fundamental mechanism, the existing therapeutic strategies for pain offer finite efficacy and troublesome side effects. The intricacy of the pathogenesis of pain enormously hinders the exploitation of therapeutic approaches. Ferroptosis is a novel mode of cell death characterized by mitochondrial damage, oxidative stress, massive intracellular iron accumulation, and lipid peroxidation. Multiple studies have demonstrated that ferroptosis is involved in the development of pain. We aim to focus on the underlying mechanisms by which ferroptosis participates in pain and recent findings on targeted therapies for ferroptosis in painful diseases. In this review, first, the pivotal mechanisms of ferroptosis are briefly summarized. Second, how ferroptosis participates in pain response is described. Finally, we summarized some substances that relieve pain by alleviating lipid peroxidation and iron accumulation and modulating ferroptosis. We propose that targeting ferroptosis holds tremendous promise in preventing and treating painful diseases.